Alpha blockers for treatment of ureteric stones: systematic review and meta-analysis. (1st December 2016) - Hollingsworth, John M; Canales, Benjamin K; Rogers, Mary A M; Sukumar, Shyam; Yan, Phyllis; Kuntz, Gretchen M; Dahm, Philipp
Abstract : Objective To investigate the efficacy and safety of alpha blockers in the treatment of patients with ureteric stones. Design Systematic review and meta-analysis. Data sources Cochrane Central Register of Controlled Trials, Web of Science, Embase, LILACS, and Medline databases and scientific meeting abstracts to July 2016. Review methods Randomized controlled trials of alpha blockers compared with placebo or control for treatment of ureteric stones were eligible.Two team members independently extracted data from each included study. The primary outcome was the proportion of patients who passed their stone. Secondary outcomes were the time to passage; the number of pain episodes; and the proportions of patients who underwent surgery, required admission to hospital, and experienced an adverse event. Pooled risk ratios and 95% confidence intervals were calculated for the primary outcome with profile likelihood random effects models. Cochrane Collaboration's tool for assessing risk of bias and the GRADE approach were used to evaluate the quality of evidence and summarize conclusions. Results 55 randomized controlled trials were included. There was moderate quality evidence that alpha blockers facilitate passage of ureteric stones (risk ratio 1.49, 95% confidence interval 1.39 to 1.61). Based on a priori subgroup analysis, there seemed to be no benefit to treatment with alpha blocker among patients with smaller ureteric stones (1.19, 1.00 to 1.48). Patients with larger stones treated with an alpha blocker, however, had a 57% higher risk of stone passage compared with controls (1.57, 1.17 to 2.27). The effect of alpha blockers was independent of stone location (1.48 (1.05 to 2.10) for upper or middle stones; 1.49 (1.38 to 1.63) for lower stones). Compared with controls, patients who received alpha blockers had significantly shorter times to stone passage (mean difference −3.79 days, −4.45 to −3.14; moderate quality evidence), fewer episodes of pain (−0.74 episodes, −1.28 to −0.21; low quality evidence), lower risks of surgical intervention (risk ratio 0.44, 0.37 to 0.52; moderate quality evidence), and lower risks of admission to hospital (0.37, 0.22 to 0.64; moderate quality evidence). The risk of a serious adverse event was similar between treatment and control groups (1.49, 0.24 to 9.35; low quality evidence). Conclusions Alpha blockers seem efficacious in the treatment of patients with ureteric stones who are amenable to conservative management. The greatest benefit might be among those with larger stones. These results support current guideline recommendations advocating a role for alpha blockers in patients with ureteric stones. Systematic review registration PROSPERO registration No CRD42015024169.